MECHANISMS OF HEALTH TOURISM DEVELOPMENT: CURRENT TRENDS AND PERSPECTIVES - Shpilyova, Yuliia (Collection of scientific papers «ΛΌГOΣ», 2025)
Health tourism has become an increasingly vital segment within the global tourism industry, driven by rising health awareness, advancements in medical technology, and the desire for holistic wellness. This paper investigates the fundamental mechanisms that facilitate the development of health tourism, including technological innovations, policy environments, infrastructure, and changing consumer preferences. It examines current trends such as the growth of wellness tourism, the rise of medical tourism destinations, and the integration of digital platforms that enhance accessibility and efficiency. Additionally, the study discusses the strategic role of sustainable practices and eco-friendly services in ensuring the sector’s long-term viability. The analysis highlights that a comprehensive approach encompassing technological development, regulatory support, high-quality service provision, and consumer-centric strategies is essential for fostering sustainable growth. Finally, the paper explores future perspectives, emphasizing personalized health services, digital health solutions, and sustainable tourism models as critical drivers for the evolution of health tourism in the coming decades.